Penerapan Pembelajaran Tari Sitalasari melalui Media Audio Visual pada Siswa Sekolah Menengah Pertama (SMP) Bintang Langkat - Fachrunnisa Nisa (Gesture: Jurnal Seni Tari, 2016)
This study aimed to describe the application of learning and the result of learning Sitalasari dance through audio visual on students at Bintang Langkat junior high school. In this discussion using the theories related to research topics such as audio visual theory and the result of learning. The method used quantitative methods. Population in the course of a study as well as an example of a study Bintang Langkat junior high school. The data collection technique consisted of field observation and test. Based on this study, it can be seen that through the audio visual media student the result of learning in the material in class VII Sitalasari Bintang Langkat Junior high school. Ratings were used in this study is the assessment of psychomotor (skill) and attitude. In psychomotor assessment results obtained after the study is fairly good student the result of learning, namely the amount of the average value of students reached 75.5% of students who achieve mastery of 25 people and students who do not achieve mastery of 5 people. The result are considered sufficient because it meet the of specified benchmark by 83.33% of student who complete and 16.66% of students who do not achieve mastery. Assessment of student the result of learning with attitudes, values, excellent students there are eight people, the percentage was 26.67% of students with good people grades there are 17 people, the percentage is 56.66% on sufficent student score 5 people percentagenya is 16.67.